Porous Carbons: Structure‐Oriented Design and Versatile Applications - Tian, Wenjie; Zhang, Huayang; Duan, Xiaoguang; Sun, Hongqi; Shao, Guosheng; Wang, Shaobin (Advanced functional materials, 2020)
Porous carbon materials have demonstrated exceptional performance in a variety of energy‐ and environment‐related applications. Over the past decades, tremendous efforts have been made in the coordinated design and fabrication of porous carbon nanoarchitectures in terms of pore sizes, surface chemistry, and structure. Herein, structure‐oriented carbon design and applications are reviewed. The unique properties of porous carbon materials that offer them promising design opportunities and broad applicability in some representative fields, including water remediation, CO2 capture, lithium‐ion batteries, lithium–sulfur batteries, lithium metal anodes, Na‐ion batteries, K‐ion batteries, supercapacitors, and the oxygen reduction reaction are highlighted. Then, the most up‐to‐date strategies for structural control and functionalization of porous carbons are summarized, toward tailoring microporous, mesoporous, macroporous, and hierarchically porous carbons with disordered or ordered, amorphous or graphitic structures. Meanwhile, the emerging features of these structures in various applications are introduced where applicable. Finally, insights into the challenges and perspectives for future development are provided. Herein, the structure–property relationships of porous carbon materials in water remediation, carbon capture, lithium‐ion batteries, lithium–sulfur batteries, Li metal anodes, Na‐ion batteries, K‐ion batteries, supercapacitors, and oxygen reduction reactions are proposed. The recent progress in structural control and functionalization of porous carbons are also summarized, in terms of achieving microporous, mesoporous, macroporous, and hierarchically porous carbons.